Epistemologi Hukum Islam: Satu Pengenalan - Abdul Rahim, Rahimin Affandi (Jurnal Usuluddin, 2002)
This article tries to introduce the concept of Islamic legal epistemology, a terminology that has been widely used in the discipline of Islamic theology. It explores the significance of such terminology in modern as well as classical knowledge. The article, then proposes with detail explanation, the creation of Islamic legal epistemology in the field of Shariah.